Soil Greenhouse Gases: Relations to Soil Attributes in a Sugarcane Production Area - Bicalho, Elton da Silva [UNESP]; Moitinho, Mara Regina [UNESP]; Teixeira, Daniel De Bortoli [UNESP]; Panosso, Alan Rodrigo [UNESP]; Spokas, Kurt Arnold; La Scala, Newton [UNESP] (Soil Sci Soc Amer, 2017)
The production of the main soil greenhouse gases (GHG: carbon dioxide [CO2], methane [CH4,] and nitrous oxide [N2O]) is influenced by agricultural practices that cause changes in soil physical, chemical, and biological attributes, directly affecting their emission to the atmosphere. The aim of this study was to investigate the infield soil carbon dioxide emissions (F-CO2) and soil CO2, methane, and nitrous oxide production potentials (P-CO2, P-CH4, and P-N2O, respectively) under laboratory conditions and their relationship to soil attributes in a mechanically harvested sugarcane area. Soil carbon dioxide emissions presented an infield average emission value of 1.19 mu mol CO2 m(-2) s(-1), while GHG production in the laboratory was 2.34 mu g C-CO2 g(-1) soil d(-1) and 0.20 ng N-N2O g(-1) soil d(-1) for P-CO2 and P-N2O, respectively. No significant production or oxidation was observed for CH4. Factor analysis showed the formation of two independent processes that explained almost 72% of the total variance observed in the data. The first process was related to F-CO2 transport and its relation to soil physical attributes such as microporosity, macroporosity, the C/N ratio, soil moisture, and soil bulk density, showing the dependence between F-CO2 and soil porosity. The second process was related to soil CO2 and N2O production potentials under laboratory conditions and their relation to soil chemical attributes such as the sum of bases, pH, and available phosphorus, which affect microbial activity and contribute to GHG production. Although presented as independent, these processes are coupled and occur simultaneously in the soil, in addition to providing information about their variability and showing if the infield emissions are due to gas transport processes or soil carbon levels and their quality.